Evaluation of Percentage of Damaged Drugs at Gondomanan Primary Health Center in Yogyakarta - Titami, Arina; Andriani, Yuni; Saputra, Doni (Sahabat Publikasi Kuu, 2025)
Background: The proper storage and distribution of drugs is very important to ensure the effects of drugs in the body and all drugs should be stored in the right storage place. Improper drug storage can cause damage to drugs that can endanger patients and health services themselves. Objective: This study aims to evaluate the drug storage process, specifically the percentage of damaged drugs, at the Gondomanan Primary Health Center in Yogyakarta. Method: The research was conducted using a descriptive observational approach with a cross-sectional design. Data were collected using a checklist referring to Peraturan Menteri Kesehatan Republik Indonesia Nomor 74 Tahun 2016 and Petunjuk Teknis Standar Pelayanan Kefarmasian di Puskesmas Tahun 2019. Result: The percentage of damaged drugs at the Gondomanan Primary Health Center in Yogyakarta is 0%. Conclusion: The percentage of damaged drugs at the Gondomanan Primary Health Center in Yogyakarta is by standards based on Peraturan Pemerintah Kesehatan Republik Indonesia Nomor 74 Tahun 2016 and Petunjuk Teknis Standar Pelayanan Kefarmasian di Puskesmas Tahun 2019.